Functional characterisation of the methionine sulfoxide reductase repertoire in Trypanosoma brucei - Guerrero, Sergio Adrian (2017)
To combat the deleterious effects that oxidation of the sulfur atom in methionine to sulfoxide may bring, aerobic cells express repair pathways involving methionine sulfoxide reductases (MSRs) to reverse the above reaction. Here, we show that Trypanosoma brucei, the causative agent of African trypanosomiasis, expresses two distinct trypanothione-dependent MSRs that can be distinguished from each other based on sequence, sub-cellular localisation and substrate preference. One enzyme found in the parasite´s cytosol, shows homology to the MSRA family of repair proteins and preferentially metabolises the S epimer of methionine sulfoxide. The second, which contains sequence motifs present in MSRBs, is restricted to the mitochondrion and can only catalyse reduction of the R form of peptide-bound methionine sulfoxide. The importance of these proteins to the parasite was demonstrated using functional genomic-based approaches to produce cells with reduced or elevated expression levels of MSRA, which exhibited altered susceptibility to exogenous H2O2. These findings identify new reparative pathways that function to fix oxidatively damaged methionine within this medically important parasite.